Influence of applied electric field annealing on the microwave properties of (Ba0.5Sr0.5)TiO3 thin films - Cho, Kwang-Hwan; Lee, Chil-Hyoung; Kang, Chong-Yun; Yoon, Seok-Jin; Lee, Young-Pak (AMER INST PHYSICS, 2007)
The effect of heat treatment in electric field on the structure and dielectric properties at microwave range of rf magnetron sputtering derived (Ba0.5Sr0.5)TiO3 thin films have been studied. It has been demonstrated that postannealing in the proper electric field can increase the dielectric constant and the tunability. The increased out-of-plane lattice constant in the electric-annealed films indicated the formation of small polar regions with tetragonal structure, which are responsible for the increased dielectric constant and tunability. It was proposed that the segregation of Ti3+ ions caused by electric annealing could induce the formation of BaTiO3-like regions, which are ferroelectric at room temperature. And in dielectric loss, as the Ti-O bonding lengths increase, the energy scattering on the ferroelectric mode also increases. So, the value of dielectric loss is slightly increased. (C) 2007 American Institute of Physics.
Keywords: TEMPERATURE; BAXSR1-XTIO3; FREQUENCY; SRTIO3